Konsep Pembaharuan Pendidikan Islam Di Madrasah dan Perguruan Tinggi Islam Di Indonesia - Asmawi HM (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2020)
The development of Islamic education in the archipelago has faced a variety of social changes ranging from the kingdom-empire era, the colonial period, the period of independence, the old order, the new order, until the fifth year of the new millennium. Changes have occurred, which initially took the form of traditional education in the form of recitation in homes, prayer rooms, mosques and also in its development also equipped or transformed itself into schools as the physical appearance of the building with modern facilities and management. In terms of the material being taught there has also been a development from what was originally, only teaching Islamic teachings and studying the Qur'an, then turning into practical worship, continuing to study the book, then leading to religious teaching in the form of selected curriculum such as monotheism / faith, morals, jurisprudence, hadith, interpretation, the history of Islam and Arabic. Colonialism has introduced a modern education model both in terms of management, teaching technology and the material taught there are pure and some have adopted or adapted Islamic education in the Middle East and the Western world.